Evaluation of Acrylamide Levels in Arabica (Coffea arabica) and Robusta (Coffea canephora) Coffee Roasting Variations for Nutraceutical Capsules - Juwariyah, Putri Siti; Rachma, Firstca Aulia; Alighiri, Dante (Integrated Research and Testing Laboratory (LPPT) Universitas Gadjah Mada, 2026)
Coffee roasting is an essential process that determines the flavor and aroma of coffee, yet it also contributes to the formation of acrylamide, a carcinogenic compound. Acrylamide is produced as a by-product of the Maillard reaction, which occurs between reducing sugars and amino acids at high roasting temperatures. This study aimed to evaluate acrylamide content in Arabica coffee (Coffea arabica) and Robusta coffee (Coffea canephora) under different roasting levels, and to assess its safety for nutraceutical capsule formulation. The experimental procedure included roasting beans at three levels (light, medium, and dark). Acrylamide analysis was performed using UV-Vis spectrophotometry with the standard addition method. Data were analyzed using Kruskal–Wallis and Mann–Whitney tests with JASP software. Results showed that acrylamide levels increased with increasing roasting time in both Arabica and Robusta coffee. The lowest acrylamide concentrations were observed at 10 minutes of roasting, particularly in the n-hexane fraction measuring 72.1154 µg/kg in Arabica coffee and 109.6825 µg/kg in Robusta coffee, while the highest levels were detected in the water fraction at 20 minutes of roasting, reaching 299.8834 µg/kg in Arabica coffee and 400.5265 µg/kg in Robusta coffee. Statistical analysis confirmed that roasting variations significantly affected acrylamide formation (p < 0.05), whereas no significant difference was found between coffee types (p > 0.05). Although the n-hexane fraction yielded the lowest acrylamide content, ethyl acetate at 10 minutes of roasting was identified as the optimal condition, as it produced relatively low acrylamide levels (124.1045 µg/kg in Arabica and 136.8083 µg/kg in Robusta) while preserving bioactive compounds suitable for nutraceutical formulation. Evaluation of granule quality and capsule characteristics indicated that all parameters met standard requirements. In conclusion, nutraceutical capsules can be formulated from the ethyl acetate fraction of coffee roasted for 10 minutes, ensuring safety and functional benefits.